Android Interactive Multimedia in Zakat Fitrah Learning: Pengembangan Multimedia Interaktif Android pada Pembelajaran Zakat Fitrah - Yuningsih, Noneng; Wahyudin, Wahyudin; Maskur, Maskur (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital technology integration has become an essential component of contemporary elementary education, particularly to support interactive and student-centered learning environments. Specific Background: In Islamic Religious Education, zakat fitrah instruction at SDN 3 Mulyasari remains dominated by lecture-based methods and limited media variation, resulting in low student participation and learning activity despite widespread Android device ownership. Knowledge Gap: Existing Android-based learning media for zakat fitrah are limited in contextual design and have not sufficiently addressed student participation and activity at the elementary level. Aims: This study aimed to develop Android-based interactive learning multimedia for zakat fitrah using the ADDIE research and development model and to examine changes in student participation and learning activity. Results: The developed multimedia, validated by media, material, and language experts, achieved a feasibility score of 90.5%. Student participation increased from 72.30 to 81.10, while learning activity rose from 69.10 to 81.60, with paired sample t-test results indicating statistically significant differences. Novelty: This study presents a contextually designed Android interactive multimedia product specifically developed for zakat fitrah learning at the elementary school level. Implications: The findings indicate that Android-based interactive multimedia can serve as an alternative digital learning medium to support active participation and learning activity in Islamic Religious Education. Highlights • Android-Based Multimedia Demonstrates High Feasibility Validation• Student Participation Shows Measurable Positive Change• Learning Activity Scores Increase After Multimedia Use Keywords Interactive Learning Multimedia; Android-Based Learning; Zakat Fitrah Education; Student Participation; Learning Activity